2020
DOI: 10.1002/adfm.201909535
|View full text |Cite
|
Sign up to set email alerts
|

As‐Cast Ternary Organic Solar Cells Based on an Asymmetric Side‐Chains Featured Acceptor with Reduced Voltage Loss and 14.0% Efficiency

Abstract: A new small‐molecule nonfullerene acceptor based on the benzo[1,2‐b:4,5‐b′]dithiophene (BDT) fused central core with asymmetrical alkoxy and thienyl side chains, namely TOBDT, is designed and synthesized. The alkoxy unit helps narrow the bandgap, and thienyl side chain helps enhance the intermolecular interaction. As a result, TOBDT is suitable to match the deep‐lying highest occupied molecular orbital (HOMO) of polymer donor PM6. Then, a strong crystalline acceptor IDIC is introduced as the third component to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
(58 reference statements)
0
33
0
Order By: Relevance
“…The smaller energetic disorder could effectively suppress the ΔE non-rad in the ternary cells. [63,64] The reduced energetic disorder could be due to the fact that the highly crystalline DRTB-T-C4 decreased π-π stacking distance and enlarged crystal coherence length in the ternary blend. [34,65,66]…”
Section: Resultsmentioning
confidence: 99%
“…The smaller energetic disorder could effectively suppress the ΔE non-rad in the ternary cells. [63,64] The reduced energetic disorder could be due to the fact that the highly crystalline DRTB-T-C4 decreased π-π stacking distance and enlarged crystal coherence length in the ternary blend. [34,65,66]…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a PCE of 14.0 % for the as-cast ternary device based on TOBDT was achieved. [42] In addition, Zhan and Yan groups reported the conjugated side-chain (e. g. alkylphenyl) was also directly connected with sp 2 -hybridized C atoms of the central core (TPBT) of Y-series SMAs (BTP-PhC6, m-BTP-PhC6, see Figure 1) to investigate the effect of the conjugated side-chain hindrance and orientation on intermolecular aggregation and solar cell performance of SMAs. [43,44] The second approach to introduce conjugated side chains is realized by p-π conjugation effect between sp 2 -hybridized N atom and aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…For SMAs, it is well known that the flexible side chain attached on backbone plays a critical role in improving the efficiency of SMAs, which not only endows SMAs with good solubility to meet the requirement of solution processing, but also provides steric hindrance to control the molecular packing and orientation. [ 24–29 ] Numerous studies have reported about the impact of the types, lengths, sizes, and positions of the side chains on SMAs. [ 30–39 ] For example, Yang and co‐workers reported that altering the side chain from alkylphenyl (IDTCN) to alkyl (IDTPC) could enhance the molecular packing in IDT‐based SMAs, and a high PCE of 12.20% was achieved for IDTPC‐based device.…”
Section: Introductionmentioning
confidence: 99%